2002
DOI: 10.1006/jsco.2002.0525
|View full text |Cite
|
Sign up to set email alerts
|

Derivations and Radicals of Polynomial Ideals over Fields of Arbitrary Characteristic

Abstract: The purpose of this paper is to give a complete effective solution to the problem of computing radicals of polynomial ideals over general fields of arbitrary characteristic. We prove that Seidenberg's "Condition P" is both a necessary and sufficient property of the coefficient field in order to be able to perform this computation. Since Condition P is an expensive additional requirement on the ground field, we use derivations and ideal quotients to recover as much of the radical as possible. If we have a basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This is a classical, standard problem in symbolic computation. We refer to [13,15,17] for the related work. So, we do not focus on how to compute generators of I(Y ) in this paper.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…This is a classical, standard problem in symbolic computation. We refer to [13,15,17] for the related work. So, we do not focus on how to compute generators of I(Y ) in this paper.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The problem of finding generators of radical ideals in polynomial rings is addressed in [40], from a computational point of view.…”
Section: Definition 14mentioning
confidence: 99%
“…The first radical ideal algorithms assumed characteristic 0. However, in recent publications algorithms have been suggested that compute radical ideals over base fields which are finitely generated over a finite field or over Q (see [11,16,19]).…”
Section: Algebraic Groupsmentioning
confidence: 99%